MnBr2-catalyzed direct and site-selective alkylation of indoles and benzo[h]quinoline - Jagtap, Rahul A.; Verma, Suryadev K.; Punji, Benudhar (Organic Letters, 2020)
Manganese-catalyzed regioselective C-H alkylation of indoles and benzo[h]quinoline with a variety of unactivated alkyl iodides is reported. Unlike other Mn-catalyzed C-H functionalization, this protocol does not require a Grignard reagent base and employs a simple and inexpensive MnBr2 as a catalyst. This method tolerates diverse functionalities, including fluoro, chloro, bromo, iodo, alkenyl, alkynyl, pyrrolyl, and carbazolyl groups. The alkylation proceeds through a single-electron transfer pathway comprising reversible C-H manganesation and involving an alkyl radical intermediate.

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

Copper-catalyzed regioselective C-H alkylation of phenol derivatives with unactivated alkyl chlorides: manifesting a Cu(I)/Cu(III) pathway - Verma, Suryadev K.; Punji, Benudhar (Journal of Catalysis, 2024)
The use of unactivated alkyl chlorides in regioselective C -H alkylation is a highly challenging process with diverse applications of alkylation strategy in drug discovery and agrochemistry. In this work, we report an efficient and cost-effective copper -catalyzed protocol for the coupling of unactivated alkyl chlorides with the C -H bond of phenol derivatives via 2-pyridinyl chelation assistance. The reaction shows a high level of regioselectivity, leading to an exclusive ortho alkylation and providing a broad scope with the endurance of numerous functionalities such as silyl, ether, thioether, pyrrolyl, indolyl, carbazolyl groups, including alkyl bearing fatty alcohol, nonylphenol, and vitamin E. Detailed mechanistic investigations suggest that the alkylation occurs through a two -electron oxidative addition of alkyl chloride to an active Cu(I) species. Deuterium labeling and kinetics experiments indicate a facile and reversible C -H bond activation process. Overall, the alkylation follows a Cu(I)/Cu(III) pathway involving chelation-assisted smooth C -H metalation and rate -limiting C-Cl oxidative addition of alkyl chloride.

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones

Nickel-catalyzed regioselective C―H alkynylation of pyridones and isoquinolinones using alkynyl bromides - Verma, Suryadev K.; Patil, Harshal R.; Punji, Benudhar (ChemCatChem, 2025)
A straightforward and efficient protocol for the regioselective C & horbar;H alkynylation of 2-pyridones and isoquinolinones with bromoalkynes under nickel catalysis is described. The alkynylation reaction is enabled by a simple and inexpensive Ni(OTf)2/tBubpy catalyst system and uses easily accessible bromoalkynes. The protocol demonstrates a broad substrate scope with up to 95% yield (42 examples) and accommodates synthetically valuable functionalities, such as halides, trifluoromethyl, nitrile, ether, thioether, alkyl silanes, and alkene, as well as heteroarene moieties like pyridinyl, furanyl, and thiophenyl. The pyridinyl directing group on alkynylated 2-pyridones can be smoothly removed to give C6-alkynylated free NH-pyridone. Preliminary mechanistic studies suggest that the alkynylation proceeds via a 2e- oxidative addition pathway involving crucial C & horbar;H activation.
Keywords: alkynylation; C & horbar; H Activation; Mechanism; Nickel; pyridones